Pengembangan Produk Minuman ES’BOYO Pada Kegiatan Wirausaha Merdeka Kampus Guna Meningkatkan Inovasi Kreatifitas UMKM Lokal - Viona Eka Putri Mardiono (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
This community service discusses the initiative to develop a beverage product called ES'BOYO through the Independent Campus Entrepreneur program. The main focus of this activity is to encourage innovation and creativity among local Micro, Small, and Medium Enterprises (MSMEs). By involving students as agents of change, this activity aims to enrich the entrepreneurial ecosystem on campus and support the development of competitive local products. The product development process includes a market study stage to understand consumer needs and preferences, ES'BOYO product design that combines traditional flavors with an innovative touch, and product trials in the local market. These steps are designed to increase the competitiveness of local MSMEs by providing added value through unique and attractive products for consumers. In addition to the product development aspect, this activity also focuses on involving students in developing entrepreneurial skills, building business networks, and understanding local market dynamics. The results of this service are expected to have a positive impact, not only in increasing sales of ES'BOYO products, but also in increasing public awareness of the importance of supporting local MSMEs and local wisdom-based product innovation. Overall, this article describes a real effort in supporting entrepreneurial ecosystems at the campus level to strengthen contributions to the development of local MSMEs and create an environment that stimulates creative innovation among students